Creativity and Neo-Patristic Synthesis in Fr. Georges Florovsky’s Thought System (Princeton Insights) - Torosyan, Rousssina (Forum Theologicum Sardicense, 2025)
Rousssina Torosyan, Creativity and Neo-Patristic Synthesis in Fr. Georges Florovsky's Thought System (Princeton Insights). This article discusses the creative and spiritual perception of life of father George Florovsky. It underlines the role creativity has for understanding his theology and possibly penetrating his system of though. In that perspective is also addressеd his concept of nepotistic synthesis, by showing the connection that exist between creativity and charismatic theology in the dynamic of love. The article suggests that creativity in its graceful meaning, may be the key of decoding his concept and understanding his spiritual message.